2008
DOI: 10.1016/j.ejcts.2007.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Jugular venous valved conduit (Contegra®) matches allograft performance in infant truncus arteriosus repair☆

Abstract: JVV does match allograft performance and may be advantageous. It is an appropriate first choice for repair of truncus arteriosus, and perhaps other small infants requiring RVOT reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 28 publications
8
62
2
2
Order By: Relevance
“…Patient-prosthesis mismatch has been cited as a reason for early failure and, therefore, there has been a demand for small pediatric allografts (<12 mm). [16] In conclusion, our study results suggest that Contegra conduit may be used for right ventricular outflow tract reconstruction in small infants with truncus arteriosus. Early surgical results are…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Patient-prosthesis mismatch has been cited as a reason for early failure and, therefore, there has been a demand for small pediatric allografts (<12 mm). [16] In conclusion, our study results suggest that Contegra conduit may be used for right ventricular outflow tract reconstruction in small infants with truncus arteriosus. Early surgical results are…”
Section: Discussionmentioning
confidence: 80%
“…The rates of freedom from conduit stenosis at three years were better for Contegra (96 to 69%). [16] It was also reported that the Contegra conduit responded better to catheter interventions, when stenosis developed. Neukamm et al [17] described that necessity for reoperations within the first two years was significantly lower for Contegra grafts than for non-blood group compatible cryopreserved homografts, two of 78 (2.6%) and eight of 20 (40.0%), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricle to left ventricle pressure ratio development and freedom from explantation/ redo were equal for the Contegra conduits and homografts 3 . The 3-year freedom from replacement for in-conduit stenosis was 96 ± 4% for the Contegra and 69 ± 8% for allograft 28 .…”
Section: Shi-minyuan Contegra Valved Bovine Conduitmentioning
confidence: 96%
“…structural continuity between the wall of the jugular vein of the conduit and the valve leaflets, which provides optimal hemodynamics because of the ideal effective orifice area b. unlimited "off-the-shelf" availability in sizes from 12 to 22 mm diameter, representing a good alternative to the homograft shortage, particularly in the smaller sizes c. availability of a long length at both inflow and outflow that obviates the need for either proximal or distal augmentation; this facilitates conduit tailoring and positioning which helps to avoid potential distortion and sternal compression d. exceptional reports of antigenic reaction, due to glutaraldehyde fixation In contrast to the good clinical results obtained in several institutions (37)(38)(39)(40)(41)(42)(43)(44)(45), a disturbing sequence of publications reported stenosis at the level of the distal anastomosis of the conduit, with proximal conduit dilatation, aneurysm or pseudo-aneurysm, in between 6 and 50% of patients (39,40,42,(46)(47)(48)(49)(50)(51)(52)(53)(54).…”
Section: Bovine Jugular Veinmentioning
confidence: 99%
“…The bovine jugular vein (Contegra®, Medtronic Inc., Minneapolis, MN), containing a trileaflet valve, was introduced into clinical practice as an alternative to the use of homografts in 1999 and has provided encouraging results in several reported clinical series, with follow-up reaching more than 10 years (37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Bovine Jugular Veinmentioning
confidence: 99%